2021
DOI: 10.1099/ijsem.0.005001
|View full text |Cite
|
Sign up to set email alerts
|

Novosphingobium decolorationis sp. nov., an aniline blue-decolourizing bacterium isolated from East Pacific sediment

Abstract: Aniline blue-decolourizing bacterial strain 502str22T, isolated from sediment collected in the East Pacific, was subjected to characterization by a polyphasic taxonomic approach. Phylogenetic analyses based on 16S rRNA gene sequences revealed that strain 502str22T belongs to the genus Novosphingobium , with closely related type strains ‘ Novosphingobium profundi … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Recent studies have shown that Sphingobacteriaceae has the ability to degrade zearalenone and vomitoxin (He, 2017). Novosphingobium species are renowned for their ability to adapt metabolically and their significant potential for effectively addressing pollution challenges (Liu et al 2021;Chen et al 2021). So it is hypothesized that Novosphingobium sp.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that Sphingobacteriaceae has the ability to degrade zearalenone and vomitoxin (He, 2017). Novosphingobium species are renowned for their ability to adapt metabolically and their significant potential for effectively addressing pollution challenges (Liu et al 2021;Chen et al 2021). So it is hypothesized that Novosphingobium sp.…”
Section: Discussionmentioning
confidence: 99%
“…All strains are negative for αmannosidase and αfucosidase activities. * Data were obtained from references [6] and [52]. +, Positive; -, negative, w, weakly positive; N, unknown.…”
Section: Physiologymentioning
confidence: 99%